2011
DOI: 10.1039/c1jm11434d
|View full text |Cite
|
Sign up to set email alerts
|

In situ preparation of functionalized graphene oxide/epoxy nanocomposites with effective reinforcements

Abstract: In order to obtain homogeneous dispersion and strong filler-matrix interface in epoxy resin, graphene oxide was functionalized via surface modification by hexachlorocyclotriphosphazene and glycidol and then incorporated into epoxy resin to obtain nanocomposites via in situ thermal polymerization. The morphology of nanocomposites was characterized by scanning electron microscopy and transmission electron microscopy, implying good dispersion of graphene nano-sheets. The incorporation of functionalized graphene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
251
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 382 publications
(270 citation statements)
references
References 108 publications
(115 reference statements)
16
251
0
3
Order By: Relevance
“…An interesting work shows that functionalized graphene oxide (FGO) with hexachlorocyclo-triphosphazene (HCTP) enhances the mechanical property, electrical property and thermal stability of epoxy resin. 19 A further study verifies that functionalized GO with HCTP can obviously increase the char yield and decrease the peak heat release rate (pHRR), CO release rate and CO 2 release rate in polystyrene. 20 Other significant research demonstrates that functionalized GO with low molecular intumescent flame retardant not only improves the dispersion of graphene but also effectively increases the flame retardancy of ethylene/vinyl acetate nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting work shows that functionalized graphene oxide (FGO) with hexachlorocyclo-triphosphazene (HCTP) enhances the mechanical property, electrical property and thermal stability of epoxy resin. 19 A further study verifies that functionalized GO with HCTP can obviously increase the char yield and decrease the peak heat release rate (pHRR), CO release rate and CO 2 release rate in polystyrene. 20 Other significant research demonstrates that functionalized GO with low molecular intumescent flame retardant not only improves the dispersion of graphene but also effectively increases the flame retardancy of ethylene/vinyl acetate nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed reviews on graphene research have been published [5,6], specifically regarding its use as polymer reinforcement. The majority of the early research was based on graphene oxide [7][8][9][10], which can be easily exfoliated and dispersed in epoxy due to the attached functional groups. However, these functional groups reduce the mechanical properties and their weight causes wrinkling of the graphene sheets [11].…”
Section: Introductionmentioning
confidence: 99%
“…Because of oxygen functional groups, graphene oxide can be further functionalized which can effectively increase the reactive points on the GO surface, bring extra advantages to improve the dispersion and interactions of GO in polymer matrices. Many studies have reported significant improvement in polymer properties with the incorporation of functionalized GO [9,10]. One study reported that the less oxidized GO was more effective than nearly fully oxidized GO in terms of reinforcing polymers.…”
Section: Introductionmentioning
confidence: 99%